2015
DOI: 10.1039/c5ra14057a
|View full text |Cite
|
Sign up to set email alerts
|

Pd1/BN as a promising single atom catalyst of CO oxidation: a dispersion-corrected density functional theory study

Abstract: Single metal atom catalysts exhibit extraordinary activity in a large number of reactions, and some two-dimension materials (such as graphene and h-BN) are found to be the prominent support to stabilize the single metal atom. The CO oxidation reaction on single Pd atom supported by two-dimensional h-BN is investigated systematically by using dispersion-corrected density functional theory study. The great stability of the h-BN supported single Pd atom is revealed, and the single Pd atom prefers to stay at the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 34 publications
5
40
0
Order By: Relevance
“…32,61 Moreover, a previous study has shown that the HOMO of the CO molecule (5s) has weight mainly around the C atom, 62 indicating that CO always acts as a donor when its C end points to the anchoring atom. The current phenomenon is similar to the positively charged CO over Al/graphene, 28 Pd/BN 56 and Pt/BNNT. 63 Both the 5s and 1p orbitals of CO hybridize with the Ag-4d states in the energy range from À8 eV to À6 eV, and the two Ag-4d peaks near the Fermi level also overlap with the 2p* orbitals of CO, confirming the strong interaction between Ag and CO.…”
Section: Adsorption Of Species Involved In the Co Oxidation Over Ag 1supporting
confidence: 50%
“…32,61 Moreover, a previous study has shown that the HOMO of the CO molecule (5s) has weight mainly around the C atom, 62 indicating that CO always acts as a donor when its C end points to the anchoring atom. The current phenomenon is similar to the positively charged CO over Al/graphene, 28 Pd/BN 56 and Pt/BNNT. 63 Both the 5s and 1p orbitals of CO hybridize with the Ag-4d states in the energy range from À8 eV to À6 eV, and the two Ag-4d peaks near the Fermi level also overlap with the 2p* orbitals of CO, confirming the strong interaction between Ag and CO.…”
Section: Adsorption Of Species Involved In the Co Oxidation Over Ag 1supporting
confidence: 50%
“…Coordinative species around the metal atoms have been demonstrated to participate in the activation/stabilization of substrates or intermediates in some reactions . While the Mars–Van Krevelen mechanism was often proposed for CO oxidation on oxide‐supported atomically dispersed metal catalysts, the Langmuir–Hinshelwood mechanism and the Eley–Rideal mechanism were more plausible for single‐metal‐atom catalysts on supports without metals, such as BN . In some reactions, the distinct coordinative environment and electronic structure of atomically dispersed metal atoms on these supports make them superior to their oxide‐supported counterparts.…”
Section: Atomically Dispersed Metal Catalysts On Metal‐free Supportsmentioning
confidence: 99%
“…We found a barrier of 5.5 eV from IS to hollow site 1, and 6.3 eV from IS to hollow site 2. These barriers were larger than the 3.8 and 5.3 eV barriers for the Pd-BN sheet [35]. Our results showed that, under normal conditions, Ni atoms would not diffuse significantly away from the B-vacancy sites, leading to good stability.…”
Section: Geometry and Stabilitymentioning
confidence: 61%
“…A new three-molecule process was recently reported for single Au catalytic sites in h-BN [30]. After that, the TER process for CO oxidation was also found to occur on single Co [32] and Pd [35] catalytic sites in h-BN. Reaction energies for the TER process for Ni are shown in Figure 7.…”
Section: Ter Processmentioning
confidence: 89%
See 1 more Smart Citation